Antimicrobial properties and brine shrimp toxicity of anti-cancer herbs : Pereskia bleo, Pereskia grandifolia and Strobilanthes crispus - Siew, Keng Yew; Wong, Sing King (Sarawak Biodiversity Centre, 2008)
Pereskia bleo, Pereskia grandifolia and Strobilanthes crispus are widely recognized as anti-cancer herbs among local community. The antimicrobial properties and toxicity of these herbs were analyzed. Aqueous extraction using both blending and decoction methods were used to obtain the herbal crude extracts. Antibacterial susceptible testing of the extracts was done using disc diffusion and minimum inhibition concentration (MIC) techniques. Toxicity test against brine shrimps was performed to determine the lethal dose (LD50) of those plant extracts. All the crude extracts of P. bleo, P. grandifolia and S. crispus did not show any antibacterial activities against Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Pseudomonas aeruginosa at amount up to 1000 ppm for MIC and 200 μg in disc diffusion. P. bleo and S. crispus showed LC50 values beyond 1000 ppm. The LC50 value of blended and decocted extracts of P. grandifolia was 13.34 μg/ml and 66.07 μg/ml respectively.